Caulobacter Species as a Cause of Postneurosurgical Bacterial Meningitis in a Pediatric Patient - Natalie Bridger; Andrew Walkty; Maryanne Crockett; Sergio Fanella; Kim Nichol; James A Karlowsky (Canadian Journal of Infectious Diseases and Medical Microbiology)
Caulobacter species have been rarely found to be a cause of human infection. A case of probable Caulobacter species meningitis occurring postneurosurgery in a pediatric patient is reported in the present article. Gram stain and colony morphology of the isolate were not consistent with the identification provided by commercial phenotypic identification systems. The present case illustrates the need to reconcile conflicting phenotypic test results using 16S ribosomal DNA sequencing.